2020
DOI: 10.1111/bju.15203
|View full text |Cite
|
Sign up to set email alerts
|

Rezum water vapour therapy: promising early outcomes from the first UK series

Abstract: The management of symptomatic BPH is evolving and there is now an expanding portfolio of minimally invasive surgical therapies (MISTs). These provide an attractive option for men looking for meaningful improvement in urinary symptoms, whilst avoiding the risks of adverse effects, particularly with regards to maintaining sexual function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
35
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(48 citation statements)
references
References 6 publications
5
35
1
2
Order By: Relevance
“…In contrast to some of the other MIST such as Urolift and urethral stents, Rezūm can be also used for enlarged median lobes [18]. In contrast to Aquablation and as prostate artery embolization (PAE), the Rezūm system has demonstrated to be successful in the day-case setting and this is relevant in the COVID-19 era, where the need to further reduce theater time and hospital stay is extremely important [19][20][21][22][23]. Moreover, the treatment time is short with procedures performed in office or outpatient setting thereby reducing the overall cost allowing high patient turnover.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to some of the other MIST such as Urolift and urethral stents, Rezūm can be also used for enlarged median lobes [18]. In contrast to Aquablation and as prostate artery embolization (PAE), the Rezūm system has demonstrated to be successful in the day-case setting and this is relevant in the COVID-19 era, where the need to further reduce theater time and hospital stay is extremely important [19][20][21][22][23]. Moreover, the treatment time is short with procedures performed in office or outpatient setting thereby reducing the overall cost allowing high patient turnover.…”
Section: Discussionmentioning
confidence: 99%
“…Three further studies have reported greater than 30% reduction in prostate volume. 12 , 16 , 17 The lack of specimen retrieval does represent a disadvantage of Rezum and as a consequence no histopathological analysis is possible. Little is known currently regarding interpretation of PSA values post Rezum treatment in regard to evaluation for possible prostate cancer.…”
Section: Methodsmentioning
confidence: 99%
“…To date there have been 12 studies published on Rezum, which have included 1391 patients (mean age 68.7 years, range: 46-90) (Tables 1 and 2). [9][10][11][12][13][14][15][16][17][18][19][20] Over half of these studies (n=7) have been published in the past 2 years, reflecting the increasing interest and uptake of this novel intervention. There has only been one randomized study and the remainder represent cohort studies (5x retrospective and 6 x prospective).…”
Section: Rezummentioning
confidence: 99%
See 2 more Smart Citations